2015
DOI: 10.1021/acs.jnatprod.5b00660
|View full text |Cite
|
Sign up to set email alerts
|

Stelleralides D–J and Anti-HIV Daphnane Diterpenes from Stellera chamaejasme

Abstract: Bioassay-guided fractionation of a petroleum ether extract of the roots of Stellera chamaejasme led to the isolation of seven new (stelleralides D–J, 1–7) and 12 known (8–19) daphnane diterpenoids. The structures and relative configurations of 1–7 were established on the basis of extensive spectroscopic analysis, including HRESIMS and comprehensive NMR techniques. All isolates were evaluated for anti-HIV activity in MT4 cells. All compounds tested, except 2, showed anti-HIV activity, and, especially, five 1α-a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
38
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(41 citation statements)
references
References 26 publications
3
38
0
Order By: Relevance
“…ESC is widely utilized in traditional Chinese medicine and confirmed to possess antibacterial, 24 antivirus, 25 and antitumors activities. 6,7 To explore the effects of ESC on HCC progression, the authors first detected its cytotoxicity to HCC cells and found that ESC inhibited cell proliferation in a dose-and time-dependent manner, and cell sur-vival rate had a sharp downtrend at 20 lg/mL ESC.…”
Section: Discussionmentioning
confidence: 99%
“…ESC is widely utilized in traditional Chinese medicine and confirmed to possess antibacterial, 24 antivirus, 25 and antitumors activities. 6,7 To explore the effects of ESC on HCC progression, the authors first detected its cytotoxicity to HCC cells and found that ESC inhibited cell proliferation in a dose-and time-dependent manner, and cell sur-vival rate had a sharp downtrend at 20 lg/mL ESC.…”
Section: Discussionmentioning
confidence: 99%
“…Seven novel daphnane diterpenoids, stelleralides D–J, were obtained from the roots of Stellera chamaejasme (Baotou, Inner Mongolia, China). Stelleralides F ( 413 ), G ( 414 ), and H ( 415 ) exhibited anti-HIV activities with EC 50 values of 0.93, 0.73, and 0.98 nM and SI values of >10,000, much more potent than zidovudine (EC 50 32 nM, SI ≥ 116) (Yan et al, 2015a ). Seven filicinic acid-based meroterpenoids comprised 6/6/11, 6/6/7/5, or 6/6/10 ring systems were obtained from Hypericum japonicum .…”
Section: Terrestrial Plantsmentioning
confidence: 99%
“…Molecular modeling and advanced NMR methods have been used in locating esters in the jatrophanes of Euphorbia amydaloides. 180 192 Daphne genkwa (Thymelaeaceae), 193 Gnidia polycephela (Thymelaeaceae), 194 and Stellera chamaejasme (Thymelaeaceae) 195 whilst some more tigliane (phorbol) esters with cytotoxic and anti-viral activity were obtained from Croton tiglium (Euphorbiaceae), 196,197 Daphne aurantica, 198 and Stillingia lineata (Euphorbiaceae). 199 The anti-viral activity of these compounds (e.g.…”
Section: Macrocyclic Diterpenoids and Their Cyclization Productsmentioning
confidence: 99%